A Surgical Safety Checklist for Performing Tracheotomy in Patients with Coronavirus Disease 19. (July 2020) - Portugal, Louis G.; Adams, Dara R.; Baroody, Fuad M.; Agrawal, Nishant
Performance of tracheotomy is a potential necessary step in the patient with coronavirus disease 19 (COVID-19) and prolonged mechanical ventilation. Due to viral aerosolization, tracheotomy carries a high risk of transmission of COVID-19 to the health care team performing the procedure. We share our institution's surgical safety checklist for performing tracheotomy in patients with COVID-19, including key modifications intended to mitigate risk to the surgical team.